2006
DOI: 10.1053/j.gastro.2006.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Novel Model of Antigen-Specific Induction of Bile Duct Injury

Abstract: Background & Aims-Biliary-directed inflammation is an important cause of acute and chronic liver disease. We developed and characterized a transgenic mouse model of immunemediated hepatobiliary injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Besides NK lymphocytes, other effector cells (such as CD8 + cells) may also be required to carry out epithelial injury and obstruct the duct lumen (17). In this study, we found that CD8 + T cells infiltrated within the extrahepatic bile duct remnants in 95% of the cases with BA, suggesting that cytotoxic CD8 + T cells could mediate inflammatory infiltration of the duct wall.…”
Section: Discussionmentioning
confidence: 60%
“…Besides NK lymphocytes, other effector cells (such as CD8 + cells) may also be required to carry out epithelial injury and obstruct the duct lumen (17). In this study, we found that CD8 + T cells infiltrated within the extrahepatic bile duct remnants in 95% of the cases with BA, suggesting that cytotoxic CD8 + T cells could mediate inflammatory infiltration of the duct wall.…”
Section: Discussionmentioning
confidence: 60%
“…Adoptively transfer of these naïve antigen-specific T cells, induced liver targeted inflammation. These reagents have been utilized to study biliary directed inflammation in transgenic mice with OVA expressed on biliary epithelial cells [5].…”
Section: Discussionmentioning
confidence: 99%
“…Livers were perfused with collagenase (0.1 mg/mL in PBS: Sigma, St Louis, MO) via the portal vein and mononuclear cells (MNC) isolated as described [5] on a discontinuous percoll gradient. The interface contained mononuclear >95% CD45 positive by flow cytometry.…”
Section: Hepatic Mononuclear Cells Isolation and Facs Analysesmentioning
confidence: 99%
See 2 more Smart Citations